Churg-Strauss Syndrome as an Unusual Cause of Dysphagia: Case Report - Park, Jihye (Ann Rehabil Med, 2015)
Systemic vasculitis is a rare disease, and the diagnosis is very difficult when patient shows atypical symptoms. We experienced an unusual case of dysphagia caused by Churg-Strauss syndrome with lower cranial nerve involvement. A 74-year-old man, with a past history of sinusitis, asthma, and hearing deficiency, was admitted to our department for evaluation of dysphagia. He also complained of recurrent bleeding of nasal cavities and esophagus. Brain magnetic resonance imaging did not show definite abnormality, and electrophysiologic findings were suggestive of mononeuritis multiplex. Dysphagia had not improved after conventional therapy. Biopsy of the nasal cavity showed extravascular eosinophilic infiltration. All these findings suggested a rare form of Churg-Strauss syndrome involving multiple lower cranial nerves. Dysphagia improved after steroid therapy.